2010
DOI: 10.1590/s0102-09352010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de nutrientes e parâmetros ruminais de vacas alimentadas com diferentes níveis de energia na dieta

Abstract: RESUMOAvaliou-se a influência de níveis de concentrado na dieta de bovinos. Utilizaram-se quatro vacas fistuladas no rúmen, distribuídas em quadrado latino 4x4, sobre o consumo, pH ruminal e nitrogênio amoniacal (N-NH 3 ). Foi utilizada a silagem de milho, como volumoso, e concentrado, à base de milho, sorgo, farelo de soja, casca de soja, ureia e gordura protegida. As dietas foram isoproteicas com 18,6% de proteína bruta, utilizando valores crescentes de extrato etéreo (5,7; 6,6; 7,5 e 8,4%) para os níveis de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Goularte et al (2010) found average concentrations of N-NH 3 of 37.40, 39.62, 35.59 and 34.13 mg/100 mL of rumen fluid for concentrate levels of 30, 40, 50 and 60%, respectively. It is noteworthy that high levels of N-NH 3 can mean bigger losses of nitrogen in the system, since, in order for there to be synthesis microbial protein and, consequently, use of N-NH 3 , there should be availability of carbon skeletons in synchrony with degradation protein in the rumen, which does not occur in diets with reduced starch and non-structural carbohydrates and/or sources of energy from fat, which should lead to loss of energy in the form of ATP, for processing into urea by the liver to urinary excretion, which probably did not occur in the present experiment, due to the lower concentrations of N-NH 3 .…”
Section: Resultsmentioning
confidence: 90%
“…Goularte et al (2010) found average concentrations of N-NH 3 of 37.40, 39.62, 35.59 and 34.13 mg/100 mL of rumen fluid for concentrate levels of 30, 40, 50 and 60%, respectively. It is noteworthy that high levels of N-NH 3 can mean bigger losses of nitrogen in the system, since, in order for there to be synthesis microbial protein and, consequently, use of N-NH 3 , there should be availability of carbon skeletons in synchrony with degradation protein in the rumen, which does not occur in diets with reduced starch and non-structural carbohydrates and/or sources of energy from fat, which should lead to loss of energy in the form of ATP, for processing into urea by the liver to urinary excretion, which probably did not occur in the present experiment, due to the lower concentrations of N-NH 3 .…”
Section: Resultsmentioning
confidence: 90%